PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV B SD NEGERI 42 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is the lack of science students learning outcomes, as seen from the average value of students is 74.25. Of the 40 students who reach KKM only 18 students (45%), while students who have not yet reached KKM were 22 students, KKM value specified is 70. Based on these problems need to be done penilitian class action by applying Quantum Teaching Model. This research aims to improve learning outcomes IVB grade science students of SD Negeri 42 Pekanbaru the academic year 2014/2015 the number of students 40 students consisting of 15 male students and 25 female students. This study was conducted by two cycles. At each cycle I and II consist of three meetings, which consists of two face to face meetings and one times daily test at the end of the cycle. With the implementation of Quantum Teaching applying the model, it can improve student learning outcomes IPA, it is seen from the increase in student learning outcomes from the base score is an average of 74.25 be increased by 76.5% in the first cycle and the second cycle becomes 82.875 by a margin of 8.625 points, an increase of 11.6% from the base score. The percentage of teacher activity also increased, as seen from the percentage of teacher activity, in the first cycle the first meeting be increased by 75%, then increased again by 86% and increased 14.7% from the first meeting. At the first meeting of the second cycle increased by to 89% increased 4.65% .In the second meeting of the second cycle of 97% was obtained which increased 8.98%. Aktivita percentage of students also increased, as seen from the percentage of activity in the first cycle the first meeting of the results obtained by 69% in the second meeting of student activity obtained at 79% which is an increase of 14.5%. Based on research outputs can be concluded that the adoption of the model Quantum Teaching to improve learning outcomes IPA fourth grade students of SD Negeri 42 Pekanbaru B can improve student learning outcomes and in this case achieving completeness criteria learning outcomes.Keywords: Quantum Teaching, Student Results